Digital Financial Knowledge and Its Influence on Lending Application Adoption - R. Bhuvaneshwari; Vinitha K. (Qubahan Academic Journal)
Digital lending services have introduced new risks for users. As digital financial services become more widespread, individuals especially younger generations have adapted to these technologies. However, for lower-income groups, financial well-being remains a critical concern, as governments struggle to meet their necessities. This study examines the relationships between financial knowledge (FK), digital finance (DF), financial attitude (FA), decision-making (DM), awareness (AW), and financial behavior (FB) in the context of digital lending applications. The research is grounded in Theory of Reasoned Action (TRA) and Theory of Planned Behavior (TPB) to understand user adoption and financial decision-making. The study employs a primary data collection approach, surveying frequent users of digital lending platforms. AMOS was used in this study to examine the structural relationships between financial knowledge, digital financial literacy, financial attitude, awareness, decision-making, financial behavior (mediator), and financial satisfaction (dependent variable). SEM in AMOS was chosen over traditional regression techniques because It allows for simultaneous testing of multiple relationships in one model. It can handle latent variables (e.g., financial behavior, financial attitude). It assesses direct, indirect, and mediating effects more effectively than simple regression. A sample of 180 respondents was gathered through an online survey. To analyze the data, the study utilizes (NCA) and (fsQCA). NCA is applied to identify essential factors that must be present for financial satisfaction, while fsQCA explores various configurations of financial knowledge, digital finance, and financial behavior that contribute to financial satisfaction. These methods offer a comprehensive, non-linear approach that extends beyond traditional regression-based models. Findings indicate that financial knowledge, digital finance, decision-making, awareness, and financial behavior are positively associated with financial satisfaction, while financial attitude negatively influences financial satisfaction. By integrating NCA and fsQCA, this study provides a deeper understanding of how fintech services impact financial well-being, offering practical implications for policymakers and fintech providers.